Designed to Clash? Reflecting on the Practical, Personal, and Structural Challenges of Collaborative Research in Psychiatry - Beeker, Timo; Glück, Rosa Kato; Ziegenhagen, Jenny; Göppert, Lena; Jänchen, Patrick; Krispin, Helene; Schwarz, Julian; von Peter, Sebastian (Frontiers in Psychiatry, 2021)
Background: In the field of mental health research, collaborative and participatory approaches in which mental health service users actively contribute to academic knowledge production are gaining momentum. However, concrete examples in scientific literature that would detail how collaborative research projects are actually organized, and how they deal with the inherent challenges are rare. This paper provides an in-depth description of a three-year collaborative project that took place in the wider context of a mixed-method process evaluation of innovative models of psychiatric care in Germany. Methods: The in-depth description we provide here draws on a vast body of notes and records that originated from numerous meetings and sessions. The research group continuously and systematically reflected on their collaboration itself using the interpretative method of ‘interactive interviewing’, which included that also the personal memories of the researchers were collectively re-discussed before and during the process of writing. Our concrete experiences as a group were then contextualized with and analyzed in the light of more general challenges that are central to collaborative research in general. Results: Performing collaborative research requires unconventional thinking and improvisation in order to find creative solutions for practical problems and to overcome the structural obstacles inherent to the process of academic knowledge production. An atmosphere of mutual trust and respect within the group is crucial, and continuous self-reflection or supervision can be largely beneficial. Challenges mainly originate from the vast heterogeneity that characterizes the researchers, usually including large differences in economic, cultural, and social capital. Conclusion: Collaborative research in the field of psychiatry is designed to bring together researchers with widely diverse backgrounds. Emerging conflicts are important parts of knowledge production but also exceptional opportunities to negotiate research ethics, and potential vehicles for personal growth and transformation. Success or failure of collaborative research largely depends on how divergences and conflicts are articulated, mediated, and reflected. This also holds true in the light of the power asymmetries within the research team and the structural power inherent to the engines of academic knowledge production.